FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STUNTING DI PUSKESMAS SYAMTALIRA ARON - Fitriani, Aida; Friscila, Ika; Mauyah, Nizan; Elvieta, Elvieta; Fatiyani, Fatiyani (Jurnal Medikes (Media Informasi Kesehatan), 2022)
Stunting is a nutritional problem that hurts children’s quality of life, especially in reaching the point of optimal growth and development according to their genetic potential. Stunting is caused by past chronic malnutrition or growth failure and is used as a long-term nutritional indicator. This study aims to analyze the relationship between infant birth weight, diet, and history of chronic energy deficiency with stunting at the Syamtalira Aron Health Center. This study used an analytical observational design. The approach is a cross-sectional study. The study was conducted in October 2021. The population was 38 people at the Syamtalira Aron Health Center. Sampling using a total sampling technique. The research instrument used a questionnaire. The research variables were birth weight, diet, history of chronic energy deficiency, and stunting. The data analysis of this research used univariate and bivariate analysis. Bivariate analysis was analyzed and calculated using the chi-square test with a 95% confidence level. The results of statistical analysis of the relationship between the independent variable and the dependent variable are all variables with a p-value of less than 0.05, namely birth weight p-value 0.01, diet p-value 0.01, and history of chronic energy deficiency p-value of 0.02 which means that statistic that birth weight, diet, and history of chronic energy deficiency were significantly related to stunting.